Qualitative Analysis of Technology Utilization Problems in Mathematics Learning from the Perspective of Teachers and Students - Prisnaini, Rizqi Muji; Wahyu, Wiwit; Kusno (Universitas Islam Negeri Raden Intan Lampung, 2026)
Technology integration in mathematics learning offers opportunities to make abstract concepts more concrete, interactive, and accessible. However, its implementation in schools often faces challenges related to teacher competence, student digital literacy, infrastructure, and learning distractions. This study aims to analyze the problems of technology utilization in mathematics learning from the perspectives of teachers and students and to identify possible strategies for optimizing its use. A qualitative phenomenological design supported by descriptive questionnaire data was employed. The participants consisted of three mathematics teachers and twelve junior high school students selected through purposive sampling because they had direct experience with technology-assisted mathematics learning. Data were collected through questionnaires, classroom observations, semi-structured interviews, and documentation. The data were analyzed using an interactive qualitative model involving data condensation, data display, coding, theme development, and conclusion drawing, while questionnaire results were examined using descriptive statistics. The findings show that technology utilization in mathematics learning was categorized as good but not yet optimal, with an average score of 3.27 for teachers and 3.16 for students. Teachers generally used technology to deliver materials and visualize mathematical concepts, but they still encountered difficulties in designing interactive and problem-solving-based learning activities. Students perceived technology as helpful for understanding mathematics, particularly through visualization, yet they also experienced distractions, application-use difficulties, and limited internet access. These findings indicate that effective technology integration requires more than device availability; it depends on teacher readiness, students’ digital literacy, learning discipline, and institutional support. Therefore, continuous teacher training, digital literacy strengthening, adequate infrastructure, and blended learning implementation are recommended to optimize technology-supported mathematics learning.